Issues of Public Social Responsibility in Great Britain and Hungary - Jakob, Nóra I; Ráczi, Zsófia (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Abstract: Social responsibility has undergone significant development in recent years. The concept has been a success for every aspect of life, personal life, the economic sphere, and finally the public sector. At present, many states are struggling with proven problems in the public sector, and social public responsibility is one of the guidelines under which a comprehensive public administration reform could be launched. In this study we examine the British and Hungarian solutions of social public responsibility. The United Kingdom's example, though ahead of us, is not sure that the fundamental legal and mindset differences make the other European countries the same way to implement the PSR that works in the Anglo-Saxon kingdom.